Herbal preparation (HemoHIM) enhanced functional maturation of bone marrow-derived dendritic cells mediated toll-like receptor 4 - Lee, Sung-Ju (BMC Complement Altern Med, 2016)
BACKGROUND: HemoHIM, which is an herbal preparation of three edible herbs (Angelicam gigas Nakai, Cnidium offinale Makino, and Peaonia japonica Miyabe), is known to have various biological and immunological activities, but the modulatory effects of this preparation on dendritic cells (DCs)-mediated immune responses have not been examined previously. DCs are a unique group of white blood cells that initiate primary immune responses by capturing, processing, and presenting antigens to T cells. RESULTS: In the present study, we investigated the effect of HemoHIM on the functional and phenotypic maturation of murine bone marrow-derived dendritic cells (BMDCs) both in vitro and in vivo. The expression of co-stimulatory molecules (CD40, CD80, CD86, MHC I, and MHC II) and the production of cytokines (IL-1β, IL-6, IL-12p70, and TNF-α) were increased by HemoHIM in BMDCs. Furthermore, the antigen-uptake ability of BMDCs was decreased by HemoHIM, and the antigen-presenting ability of HemoHIM-treated mature BMDCs increased TLR4-dependent CD4(+) and CD8(+) T cell responses. CONCLUSIONS: Our findings demonstrated that HemoHIM induces TLR4-mediated BMDCs functional and phenotypic maturation through in vivo and in vitro. And our study showed the antigen-presenting ability that HemoHIM-treated mature BMDCs increase CD4(+) and CD8(+) T cell responses by in vitro. These results suggest that HemoHIM has the potential to mediate DC immune responses.